2023
DOI: 10.3389/fendo.2023.1154824
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipocytes in the pathogenesis of atrial fibrillation: An update on basic and translational studies

Abstract: Epicardial adipose tissue (EAT) is an endocrine organ containing a host of cell types and undoubtedly serving a multitude of important physiologic functions. Aging and obesity cause hypertrophy of EAT. There is great interest in the possible connection between EAT and cardiovascular disease, in particular, atrial fibrillation (AF). Increased EAT is independently associated with AF and adverse events after AF ablation (e.g., recurrence of AF, and stroke). In general, the amount of EAT correlates with BMI or vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…In our study, male patients with diabetes mellitus, BMI ≥24 kg/m 2 , and E/A ratio <1 had a larger EAT volume in the frequent PVC cohort. Recent studies demonstrated these results ( 20 , 21 ). Both obesity and type 2 diabetes are important risk factors for AF, possibly because they both cause an expansion of EAT, which is the source of pro-inflammatory adipocytokines that can lead to microvascular dysfunction and fibrosis of the myocardium.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, male patients with diabetes mellitus, BMI ≥24 kg/m 2 , and E/A ratio <1 had a larger EAT volume in the frequent PVC cohort. Recent studies demonstrated these results ( 20 , 21 ). Both obesity and type 2 diabetes are important risk factors for AF, possibly because they both cause an expansion of EAT, which is the source of pro-inflammatory adipocytokines that can lead to microvascular dysfunction and fibrosis of the myocardium.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, our results suggested that an increase in EAT volume might not coincide with a deterioration of its qualitative aspects. Understanding these mechanisms may reveal therapeutic interventions to address qualitative changes in the EAT (Willar et al., 2023 ) and noninvasive approaches to assess qualitative changes of the EAT (Ishii et al., 2021 ; Mancio et al., 2022 ) in terms of reducing the risk of AF.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IL6, TNF and AF had been validated [51][52] and that pointed that the mechanism of C-C,N,S treating AF maybe related to in ammation. Then the gene speci c expression analysis provided a possibilities that C-C,N,S can regulate the in ammation occurred in cardiac myocytes, adipocytes and endothelial which maybe generated by liver diseases and heart diseases [53][54][55] . Subsequently, GO function and KEGG pathways analysis further explained the anti in ammation mechanism of C-C,N,S.…”
Section: Discussionmentioning
confidence: 99%